ANTIOXIDANT, ANTIBACTERIAL POTENTIAL AND HPLC ANALYSIS OF Dioscorea alata BULB - Md. Anisuzzman - -; Md. Nazmul Hasan Zilani; Sharmin Sultana Khushi; Md. Asaduzzman - --; Md. Golam Hossain - (Indonesian Journal of Pharmacy, 2016)
The purpose of the present study was to evaluate antioxidant, antibacterial potential and HPLC analysis of methanol extract of Dioscorea alata bulb. Antioxidant activity investigated by DPPH free radical scavenging assay, the IC50 value of plant extract was24.99µg/mL. Significant absorption of extract (1.317 of 1mg/mL) showed the ferric reducing activity. HPLC analysis indicated the presence of myricetin (471.53mg/100 g of dry extract) in the highest concentration. Extract showed significant zone of inhibition in antibacterial activity test. The presence of myricetin along with other detected polyphenols might contribute to antioxidant and antibacterial activities. Key words: Total Phenolic content, Myricetin, Scavenging activity, Disc diffusion